Postfeminist whiteness - Marston, Kendra (Edinburgh University Press, 2019)
In the first extended study into the politics of whiteness inherent within postfeminist cinema, Kendra Marston interrogates representations of melancholic white femininity in contemporary Hollywood cinema, arguing that the 'melancholic white woman' serves as a vehicle through which to explore the excesses of late capitalism and a crisis of faith in the American dream. This figure may be idealised or scapegoated within these films, yet strategic performances of gendered melancholia may produce benefits for white female directors and stars disadvantaged within a patriarchal industry. Examining film genres including the tourist romance, the fantasy film and the psychological thriller, the book also contains case studies of films like 'The Virgin Suicides,' 'Blue Jasmine,' 'Gone Girl' and 'The Girl on the Train.'
10.3366/edinburgh/9781474430296.001.0001
Keywords: Film; Weibliche Weiße; Melancholie; Women; White; in motion pictures; Melancholy in motion pictures